Alexander the Great’s Campaign in Basand (Baisun) - Rtveladze, Eduard V. (Anabasis. Studia Classica et Orientalia, 2018)
At the end of the episode in Curtius Rufus detailing the capture of the Rock of Sisimithres there is an intriguing event which deserves special attention (Curt. 8.2.33–40). This event in Alexander’s campaign in Central Asia, marred by great difficulties and fierce fighting, has never been the subject of a special study, although it was this march that led to the tragic death of two Macedonian heroes – Philippus, the brother of Alexander’s personal bodyguard Lysimachus, and Erigyius, one of the “illustrious generals” of the Macedonian army. They died during a campaign in Basand (Baisun). In the first period of its existence (late 4th–early 3rd century BC) Kurganzol was a tholos intended for the burial with splendor and honor of Philippus and Erigyius.